Conflitos conjugais e estratégias de resolução: percepções de um grupo focal - Costa, Crístofer Batista da (Universidade do Vale do Rio dos Sinos, 2015)
The aim of this dissertation was to investigate the reasons of conflict, their levels, the conflict resolution strategies and the reverberation of these factors on marital. This is a joint study in which quantitative data were collected through the marital conflict scale and quality through a focus group. In the quantitative stage 200 individuals responded to marital conflict scale and qualitative nine people participated in a focus group. Quantitative data were submitted to mean comparison analysis and qualitative content analysis. The survey results showed the children, the experiences in their birth family, finance, different characteristics and preferences of each spouse and the time to be together as the most evident reasons of conflict. Feelings, expectations and the willingness to dialogue are crucial to the resolution of conflicts and depend on their characteristics and the changes that occur over time of marriage. Marital conflict and resolution strategies are inherent in the conjugality, they interact systemically and they are associated as the time of marriage and personal characteristics of the couple. The topic in question needs more investigation because of its size and because it is a phenomenon that is constantly being updated.
Keywords: Casamento; Cônjuges; Conflito conjugal; Resolução de problemas; Marriage; Spouses; Marital conflict; Problem solving; ACCNPQ::Ciências Humanas::Psicologia